2005
DOI: 10.1002/ptr.1628
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical, pharmacological and toxicological aspects ofHibiscus sabdariffa L.: a review

Abstract: This article reviews the reported phytochemical, pharmacological and toxicological properties of Hibiscus sabdariffa L. (English: roselle, red sorrel; Arabic: karkade), the calyces of which are used in many parts of the world to make cold and hot drinks. Nutritionally, these contain ascorbic acid (vitamin C). In folk medicine, the calyx extracts are used for the treatment of several complaints, including high blood pressure, liver diseases and fever. The pharmacological actions of the calyx extracts include st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
282
0
18

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(306 citation statements)
references
References 58 publications
(77 reference statements)
6
282
0
18
Order By: Relevance
“…Extracts of roselle calyces are used for liver diseases, fever and high blood pressure. The calyx extracts are found to have strong in vitro and in vivo antioxidant activity (Ali et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Extracts of roselle calyces are used for liver diseases, fever and high blood pressure. The calyx extracts are found to have strong in vitro and in vivo antioxidant activity (Ali et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…2012). The antimicrobial properties of roselle were attributed to the presence of an abundance of secondary metabolites including a wide range of phenolic compounds (Ali et al, 2005). Additionally, some of these naturally occurring phenolic compounds have shown anti-carcinogenic, anti-hypertensive, anti-microbial, anti-mutagenic, anti-oxidative, and antiinflammatory properties (Kim & Lee 2003;Mckay et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In view of its reported nutritional and pharmacological properties and relative safety, H. sabdariffa and compounds isolated from it could be a source of therapeutically useful products. 9,10 Different studies, both in animal [11][12][13][14] and human models, 15,16 have shown that an extract or infusion of ST influences the atherosclerosis process, blood sugar and lipids, and BP. Lin et al 17 reported that ST infusion reduces cholesterol by 8.3-14.4% after 4 weeks.…”
Section: Introductionmentioning
confidence: 99%